Cross-Cultural Business Negotiations in Developing Markets: Comprehending the Impact of Institutional and Cultural Elements - Sasne Grosz, Annamaria; Jozsa, Laszlo; Sengsouly, Homedahack (International Review of Management and Marketing, 2024)
The article investigates cross-cultural business negotiations in Laos, paying particular attention to the complex interplay of institutional and cultural factors and their impact on negotiations in a developing South-East Asian market. Comparisons are drawn with the business cultures of Western and Central Europe, and the results of qualitative research conducted among Laotian and European businesspeople highlight the importance of cross-cultural knowledge and training. This article also provides insight into the business life of a country about which little has previously been written in the literature. Although both Western and Laotian businesspeople need to study each other’s business cultures, the openness of the Laotian people tends to guarantee long-term success.